PERBANDINGAN CITARASA BIJI KOPI (Coffea canephora A.Froehner) ANTARA PENGOLAHAN TEKNIK SANGRAI DAN ROASTING DI DESA HUJUNG LAMPUNG BARAT SEBAGAI SUMBER BELAJAR BIOLOGI SMA KELAS XII PADA MATERI TEKNOLOGI PANGAN - Winda Afriani; Suharno Zen; Anak Agung Oka (EDUBIOLOCK, 2024)
This research is motivated by the importance of coffee processing techniques in determining the final taste of robusta coffee beans. Roasting and roasting techniques are two methods that are often used, but each technique has a different effect on the quality of coffee flavor. This research aims to compare the results of processing robusta coffee beans using these two techniques. This research aims to compare the results of roasting and roasting techniques on the taste of robusta coffee beans (Coffea robusta) in Hujung Village, West Lampung. The research method used was experimental with two treatments, namely roasting and roasting techniques. Taste testing is carried out by experienced panelists using organoleptic tests. The research results show that there is a significant difference in taste between coffee beans processed using roasting and roasting techniques. The panelists preferred coffee beans processed using the roasting technique compared to coffee processed using the roasting technique, this is because coffee beans processed using the roasting technique have a stronger aroma and stronger taste compared to coffee processed using the roasting technique, data from This research shows that the average value of the hedonic scale of the panelists' liking for technical roasted coffee in terms of aroma is 4.45, taste is 4.2 and taste impression is 3.75. Meanwhile, for the roasting technique, the average of the hedonic scale for the panelists' liking for the aroma aspect was 3.7, for the taste aspect it was 3.95 and for the taste impression aspect the average was 3.55. This research can be used as a biology learning resource for Class XII high school students on food technology material, especially in understanding processing processes and their influence on product quality.